Differential expression of alternative 5' untranslated regions in mRNAs encoding rat insulin-like growth factor I. - Lowe, W L (1987)
Rat insulin-like growth factor I (IGF-I) cDNAs contain three alternative 5' untranslated sequences (termed class A, B, and C), which are associated with an identical coding region for the mature IGF-I peptide. A solution hybridization/RNase protection assay was used to simultaneously quantitate the relative abundance of IGF-I transcripts with the different 5' untranslated regions. In all the tissues studied, transcripts with the class C 5' untranslated region were most abundant. In contrast, both class A and B transcripts were tissue specific. Class A transcripts were present in moderate abundance in liver; in low abundance in kidney, lung, testes, and stomach; and were undetectable in muscle, heart, and brain; whereas class B transcripts were detected only in liver. These three classes of 5' untranslated region were also regulated independently by growth hormone. In liver, heart, kidney, and lung, growth hormone increased the abundance of class C transcripts 2- to 3-fold. In liver, growth hormone increased the abundance of the class A and B transcripts 6- to 7-fold. In lung and kidney, on the other hand, the abundance of class A transcripts was not affected by growth hormone. Thus, rat IGF-I gene transcripts contain one of three alternative 5' untranslated regions, which are expressed in a tissue-specific manner and are differentially regulated by growth hormone. Finally, cDNA probes unique to two of the three 5' untranslated regions hybridized to all three major species of IGF-I mRNA typically seen on RNA blots with a coding region probe.